Going beyond the use of internet in a village in the Amazon region - Leal, Debora; Wulf, Volker (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4222, 2018)
In this paper I briefly describe my ongoing PhD work. Together with a rural community in the Brazilian Amazon I study their use patterns of internet applications and jointly improve the technical internet infrastructure in this remote area. My work serves to support their desire for increased resilience, and sheds light on how the culture of a technology and the culture of its recipients meet and how processes of adaption can be supported by HCI researchers.